Step
*
1
1
1
1
1
1
of Lemma
rneq-if-rabs
1. v : ℤ
2. v = (((v ÷ 4) * 4) + (v rem 4)) ∈ ℤ
3. |v rem 4| < |4|
⊢ (4 < v ÷ 4 ∨ 4 < -(v ÷ 4)) 
⇒ (¬v < -4) 
⇒ 4 < v
BY
{ (Reduce -1 THEN Assert ⌜(|v rem 4| = (v rem 4) ∈ ℤ) ∨ (|v rem 4| = (-(v rem 4)) ∈ ℤ)⌝⋅) }
1
.....assertion..... 
1. v : ℤ
2. v = (((v ÷ 4) * 4) + (v rem 4)) ∈ ℤ
3. |v rem 4| < 4
⊢ (|v rem 4| = (v rem 4) ∈ ℤ) ∨ (|v rem 4| = (-(v rem 4)) ∈ ℤ)
2
1. v : ℤ
2. v = (((v ÷ 4) * 4) + (v rem 4)) ∈ ℤ
3. |v rem 4| < 4
4. (|v rem 4| = (v rem 4) ∈ ℤ) ∨ (|v rem 4| = (-(v rem 4)) ∈ ℤ)
⊢ (4 < v ÷ 4 ∨ 4 < -(v ÷ 4)) 
⇒ (¬v < -4) 
⇒ 4 < v
Latex:
Latex:
1.  v  :  \mBbbZ{}
2.  v  =  (((v  \mdiv{}  4)  *  4)  +  (v  rem  4))
3.  |v  rem  4|  <  |4|
\mvdash{}  (4  <  v  \mdiv{}  4  \mvee{}  4  <  -(v  \mdiv{}  4))  {}\mRightarrow{}  (\mneg{}v  <  -4)  {}\mRightarrow{}  4  <  v
By
Latex:
(Reduce  -1  THEN  Assert  \mkleeneopen{}(|v  rem  4|  =  (v  rem  4))  \mvee{}  (|v  rem  4|  =  (-(v  rem  4)))\mkleeneclose{}\mcdot{})
Home
Index